Vernakalant hydrochloride in the treatment of atrial fibrillation: a review of the latest clinical evidence. (April 2011) - Marinelli, Alessandro; Ciccarelli, Iacopo; Capucci, Alessandro
Pharmacological cardioversion is still a fundamental and readily available instrument to control symptoms and promptly restore sinus rhythm in atrial fibrillation. A rapidly acting, efficacious and safe agent that targets the fibrillating atria without affecting ventricular refractoriness is highly desirable. Among newer atrial-selective antiarrhythmic agents, vernakalant is in the most advanced phase of investigation and its intravenous formulation has recently been approved in the EU for atrial fibrillation pharmacological cardioversion. The present article reviews vernakalant''s pharmacological features and safety and efficacy as emerged from clinical trials performed so far to give a comprehensive vision of available data and to discuss implications for the clinical practice in atrial fibrillation management.